Moderation of Opportunistic Behavior between Budget Participation Preparation and Managerial Performance in the Telkom Pension Fund - Retno Paryati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
A budget is a plan that is expressed quantitatively in units of money to achieve predetermined organizational goals. This study aims to determine whether there is an effect of opportunistic behavior on budgeting participation and managerial performance. Therefore, this study was conducted to see its consistency with previous studies. Researchers are interested in conducting research in the PT. Telkom Indonesia because of the phenomenon that occurs in the lack of effective managerial performance which results in opportunistic behavior related to the preparation of budget participation in the Employee Pension Fund of PT. Telkom Indonesia. This research was conducted in the PT. Telkom Indonesia Employee Pension Fund environment with the number of samples used as many as 78 employee respondents who were involved in the budgeting process. Analysis of the data used a moderating regression test (MRA) Moderated Regression Analysis with SPSS Software Version 20. The results of this study indicate that the preparation of budgetary participation has a significant effect on managerial performance, while opportunistic behavior is a moderating variable that strengthens the influence of budgetary participation on managerial performance.